STRATEGI PEMBELAJARAN ASSESMAN SEARCH: DISAIN DAN IMPLEMENTASI - Syahrial Syahrial (Universitas Batanghari Jambi, 2017)
This research is motivated by low learning result of student math in school. The low learning outcomes are influenced by the factors of learning strategies that are less varied, the saturation of students in the learning process, and the lack of involvement of learners since the beginning of learning. The main purpose of this study is to determine the effect of assessment assessment strategy on student learning outcomes, and is pre experimental research with randomized control group design only. Based on the final test of learning result obtained the average of learning result of math in experimental class 77,33 and the mean of result of learning of control class mathematics 66,67. The result of t-test analysis obtained t is equal to 2.15 and t table is equal to 1.67 at real level of 0.05 with dk equal to 46 (tcount larger ttable) means accept H1 means student's mathematics learning outcomes in ekprimen better than class control. Based on the hypothesis test it can be concluded that there is influence assessment assessment strategy on student learning outcomes mathematics.Keyword: Assessment Search